The effects of changes in prices and income on car and fuel demand in Iceland - Þórkatla Hauksdóttir 1983- (2010)
The aim of this study is to estimate the effects on gasoline demand, the demand for new cars and the development of the car fleet in Iceland from changes in income, car prices and gasoline price. Models are defined to estimate the elasticities of these demands from the year 1982 to 2008. Results for two alternative demand specifications are examined: One in which demand is assumed to be perfectly price-and income reversible and another which allows for irreversibility. The main results from the reversible model are that changes in income have great effects on number of cars in Iceland and the demand for new cars. Car prices also affect these demands, especially the demand for new cars. From this it can be assumed that taxes and all extra charges on cars can have great impact on consumer’s choice when buying a new car. The results from the irreversible model lend support to the notion that consumers do not necessarily respond in the same fashion to changes in gasoline price. The gasoline use decreases more when gasoline price rises than it increases when gasoline price drops. Umhverfis- og orkurannsóknarsjóður Orkuveitu Reykjavíkur